Critical analysis of local newspapers' design - Barbon, Krisna C.
The study, "Critical Analysis of Local Newspaper Design", gives the idea of how local newspapers in Iloilo are designed through evaluation of the four elements of design namely headline, text, photo, cutline and the over-all layout of the front page. The duration for the evaluation occurred for a span of four weeks. The subjects for the study were the seven newspapers found in Iloilo City. As a result of the evaluation, it has been found out that in headline layouting, all seven newspapers failed to be consistent in following the line-column formula and the 5-10 words headline guideline. In text layouting, the common problems are the measurements of the legs of columns and jump stories. For photos found in the front page, most of them do not have borders and with excessive use of photo clichés. The photos all look natural but do not suggest actions. For cutline, not all newspapers observed proper placement which should be outside the photo. For the overall layout, majority of the newspapers have balance. The researchers observed that there is a need to improve the front page layout of local newspapers in Iloilo City.